Hepatitis C Virus Incidence in a Cohort in Medication-Assisted Treatment for Opioid Use Disorder in New York City. (2nd September 2020) - Jordan, Ashly E; Cleland, Charles M; Wyka, Katarzyna; Schackman, Bruce R; Perlman, David C; Nash, Denis
Abstract: Background: Hepatitis C virus (HCV) incidence has increased in the worsening opioid epidemic. We examined the HCV preventive efficacy of medication-assisted treatment (MAT), and geographic variation in HCV community viral load (CVL) and its association with HCV incidence. Methods: HCV incidence was directly measured in an open cohort of patients in a MAT program in New York City between 1 January 2013 and 31 December 2016. Area-level HCV CVL was calculated. Associations of individual-level factors, and of HCV CVL, with HCV incidence were examined in separate analyses. Results: Among 8352 patients, HCV prevalence was 48.7%. Among 2535 patients seronegative at first antibody test, HCV incidence was 2.25/100 person-years of observation (PYO). Incidence was 6.70/100 PYO among those reporting main drug use by injection. Female gender, drug injection, and lower MAT retention were significantly associated with higher incidence rate ratios. Female gender, drug injection, and methadone doses <60 mg were independently associated with shorter time to HCV seroconversion. HCV CVLs varied significantly by geographic area. Conclusions: HCV incidence was higher among those with lower MAT retention and was lower among those receiving higher methadone doses, suggesting the need to ensure high MAT retention, adequate doses, and increased HCV prevention and treatment engagement. HCV CVLs vary geographically and merit further study as predictors of HCV incidence.